LLC "Daual " on the example of buildings of granite slabs for facades study of properties - Sabitov Ерлан; Ermaganbetov Айдос (Рroblems of engineering and professional education, 2023)
Keramagranit has some drawbacks: a slippery surface, the need for regular and careful maintenance. For details of our decision was to conduct a study on improving the properties of complex solutions keramagranita. These tasks allow you to use more keramagranit improve physical and mechanical properties.